Nominal rigidities and the optimal rate of inflation - Torben M. Andersen (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
This paper analyses two reasons why inflation may interfere with price adjustment so as to create inefficiencies in resource allocation at low rates of inflation. The first argument is that the higher the rate of inflation the lower the likelihood that downward nominal rigidities are binding (the Tobin argument) which implies a non-linear Phillips-curve. The second argument is that low inflation strengthens nominal price rigidities and thus impairs the flexibility of the price system resulting in a less efficient resource allocation. It is argued that inflation can be too low from a welfare point of view due to the presence of nominal rigidities, but the quantitative importance is an open question. Klassifikation:
urn:nbn:de:hebis:30-9576
Keywords: E20; E30; 330; nominal rigidities; allocative efficiency; optimal rate of inflation